Potential consequences for recruitment, power, and external validity of requirements for additional risk factors for eligibility in randomized controlled trials in secondary prevention of stroke. - Howard, S; Algra, A; Warlow, C; Rothwell, P (2006)
BACKGROUND AND PURPOSE: Eligibility criteria determine the external validity (generalizability) of the results of randomized controlled trials. To increase the number of outcome events, and hence statistical power, some recent stroke prevention trials have required additional vascular risk factors for eligibility. METHODS: To assess the merits of additional eligibility criteria in stroke prevention trials, we analyzed data from 3 trials and 1 hospital-referred series of patients with a transient ischemic attack or minor ischemic stroke. Patients were stratified according to 2 sets of additional risk factors similar to those used in recent trials (MATCH, SPORTIF and PRoFESS); risk of stroke, myocardial infarction, or vascular death was calculated in relation to the number of risk factors. RESULTS: Although the observed risk during follow-up did increase with the number of risk factors present (P<0.01 for both sets), the risks in patients with > or =1 risk factors were not substantially greater than those in all patients. Consequently, although the proportions of patients with no risk factors in the 4 cohorts differed substantially between the 2 sets of eligibility criteria (21% to 28% versus 56% to 73%), in neither case could their exclusion be justified on statistical grounds. CONCLUSIONS: The degree of patient selection introduced by use of additional vascular risk factors as eligibility criteria for trials can differ substantially between apparently similar sets of risk factors. Given that the potential for additional eligibility criteria to undermine generalizability and prolong recruitment outweighs any benefits in terms of statistical power, the exclusion of patients with no risk factors is difficult to justify.